Tracking sectoral allocation of official development assistance: a comparative study of the 29 Development Assistance Committee countries, 2011-2018 - Shuhei Nomura; Haruka Sakamoto; Aya Ishizuka; Kazuki Shimizu; Kenji Shibuya (Taylor & Francis Group, 2021)
Background: Official development assistance (ODA) is one of the most important means for donor countries to foster diplomatic relations with low- and middle-income countries and contribute to the welfare of the international community. Objective: This study estimated the sectoral allocation of gross disbursements of ODA of the 29 Development Assistance Committee (DAC) member countries of the Organisation for Economic Co-operation and Development (OECD) for the duration of 2011 to 2018, by aid type (bilateral, multilateral, and both aids). Methods: Data from the OECD iLibrary were used. The sector definition was based on the OECD sector classification. For core funding to multilateral agencies that do not specialize in each aid sector, we estimated ODA and its flows based on the OECD methodology for calculating imputed multilateral ODA. Results: For all 29 countries, during the period of 2014-2018 where data were available for all the countries, the sector with the highest average annual ODA contribution was health at 20.34 billion USD (13.21%), followed by humanitarian aid at 18.04 billion (11.72%). Humanitarian aid has increased in the sectoral share rankings in both bilateral and multilateral aid, and the sectoral share for refugees in donor countries has increased in bilateral aid. While the 29 countries show relatively similar trends for sectoral shares, some countries and sectors display unique trends. For instance, infrastructure and energy sectors in bilateral aid of Japan are particularly high accounts for 48.48% of the total bilateral ODA of the country in 2018. Conclusions: This paper evaluated ODA trends by major donors of DAC countries in the pre-COVID-19 pandemic periods. We hope that our estimates will contribute to the review of the strategic decision-making and the effective implementation of future ODA policy discussions in the DAC countries while ensuring transparency.